2020
DOI: 10.1186/s12913-020-05874-3
|View full text |Cite
|
Sign up to set email alerts
|

Improving walking speed reduces hospitalization costs in outpatients with cardiovascular disease. An analysis based on a multistrata non-parametric test

Abstract: Background To assess the association between walking speed (WS) and its improvement on hospitalization rates and costs in outpatients with cardiovascular disease. Methods Six hundred forty-nine patients participating in an exercise-based secondary prevention program were studied. Patients were divided at baseline into two groups characterized by low and high WS based on the average WS maintained during a moderate 1-km treadmill-walking test. WS and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 61 publications
(71 reference statements)
0
12
0
Order By: Relevance
“…Detailed information on the individual studies is shown in Table 2 . Six studies were observational cohort studies [ 21 23 , 28 , 29 ], two were cross-sectional studies [ 25 , 27 ], one was a decision analysis using a Markov Model [ 24 ], and one was a microsimulation [ 26 ]. All studies ( n = 10) examined the economic impact of mobility in middle-aged to aged populations.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Detailed information on the individual studies is shown in Table 2 . Six studies were observational cohort studies [ 21 23 , 28 , 29 ], two were cross-sectional studies [ 25 , 27 ], one was a decision analysis using a Markov Model [ 24 ], and one was a microsimulation [ 26 ]. All studies ( n = 10) examined the economic impact of mobility in middle-aged to aged populations.…”
Section: Resultsmentioning
confidence: 99%
“…Walking (never, seldom, sometimes, often, always) during leisure-time and healthcare expenditure in primary care Total medical expenditures Expenditure on consultations, laboratory tests and medical consultations transformed into currency by standard table (provided by Brazilian government) Walking Speed Purser et al 2005 [ 23 ] Walking speed predicts health status and hospital costs for frail elderly male veterans USA n = 1,388 Department of Veterans Affairs (VA) multicenter clinical trial Cohort study Medical or surgical patients > 65 years. Geriatric Evaluation and Management (GEM) program Multivariate models to adjust for the effect of potential socio economic confounders, assessing baseline in gait speed and absolute change over 1 year Inpatient health services use, and total costs Data on length of stay, number, and charges of inpatient consultations, rehabilitation and social work visits as available from Veterans Affairs databases Bonnini et al 2020 [ 28 ] Improving walking speed reduces hospitalization costs in outpatients with cardiovascular disease. An analysis based on a multistrata non-parametric test Italy n = 649 Exercise-based secondary prevention program Prospective cohort study Patients participating in an exercise-based secondary prevention program (average age 63) Multi-strata permutation test after propensity score matching.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Imbalances in the ANS have been shown to increase the risk of arrhythmia in CAD patients. Increments in the sympathetic nervous system (SNS) activity in CAD patients may lead to greater myocardial ischemia, which in turn, increases the SNS activity while decreasing the parasympathetic nervous system (PSNS) activity [ 25 , 26 ].…”
Section: Resultsmentioning
confidence: 99%